Bioadsorption of methyl orange and methylene blue contained in water using as bioadsorbent natural brushite (nDCPD) - Joaquín-Medina, Estefania; Patiño-Saldivar, Laura; Ardilas A., Alba A.; Salazar-Hernández, Mercedes; Hernández, Jose A. (Tecnología y ciencias del agua, 2021)
Textile industry contributes significantly to dyes water pollution like methylene blue (MB) and methyl orange (MO). In this study the equilibrium adsorption of MB and MO present in the water was investigated using nDCPD as bioadsorbent, an eco-economic and environmentally friendly material. The data isotherms showed the best fit for the Freundlich model with dyes, having the high adsorption capacity at 45 °C (179.84 mg/g) and 25 °C (165.6 mg/g) for MB and MO, respectively. Thermodynamic studies reveal that adsorption is a spontaneous and irreversible process for both dyes, however, for MB, the adsorption is endothermic, and MO is exothermic. Kinetics studies displays that the MB adsorption follows a pseudo second order kinetics (125.1 mg/g at 25 °C) while MO (193.3 mg/g at 45 °C) follow a kinetic of pseudo first order. It can be specified that nDCPD has a great affinity for removal of both dyes so this material can be used for water treatment at low cost.